Reweaving the urban fabric of the historic riverfront townscape of Masjid India, Kuala Lumpur - Mohamad Rozaly, Mohamad Zafarullah; Mohmad Shukri, Sharyzee; Abd. Latip, Nurul Syala; Abdullah, Alias (Science Publishing Corporation, 2018)
This study aims to examine the state of decline in the art of relationship between the urban river and all other elements in the historic townscape using principles of the Integrative Theory with the purpose to identify what binds townscape together and gives its sense of place and what causes the rupture. A qualitative-method case study was conducted in the Masjid India Riverfront District involving a visual survey, townscape appraisal, and content analysis on the morphology of the historic riverfront. The results show that the rupture between townscape and river as context is a product of poor walkability in a riverfront devoid of any setting for meaningful human activities, and the key to reweave the historic townscape is to rediscover what gives its meaning and sense of place.